Tribological Properties of Cyperus Pangorei Fibre Reinforced Polyester Composites(Friction and Wear Behaviour of Cyperus Pangorei Fibre/Polyester Composites). Issue 2 (1st February 2021) - Rajini, N; Mayandi, K; M, Manoj Prabhakar; Siengchin, Suchart; Ayrilmis, Nadir; Bennet, C; O. Ismail, S
ABSTRACT: This paper investigated the tribological behavior of natural fiber-reinforced polyester composites. The Cyperus pangorei (CP) fiber and polyester were used as a reinforcement material and thermosetting matrix, respectively. The composites were fabricated using compression molding technique with 40 wt% of CP fiber. Technological properties such as density, hardness, and wear of the composite specimens were determined. The density and shore D hardness of the prepared specimens were 1.0176 g/cc ± 0.106 and 87.25 ± 4.1, respectively. A pin-on-disk wear test machine was used to conduct the dry sliding wear test with constant sliding distance; various sliding velocities of 1, 2, and 3 m/s; and a range of contact pressure of 0.13–0.38 MPa. After the wear test, the surface roughness of worn specimens was measured. The specific wear rate increased when the applied load was increased on the specimen. A non-linear decrease in coefficient of friction was observed with the combination of increasing contact pressure and decreasing sliding velocity. The morphological analyses were carried out using a scanning electron microscope for the worn specimens.